Relationship Between Dental Caries and Nutritional Status Among Kindergarten Children at Darul Imarah, Aceh Besar Regency - Mardiah, Ainun; Erwandi, Erwandi; Rahayu, Eka Sri; Reca, Reca; Nuraskin, Cut Aja (PT. Riset Press International, 2025)
Dental caries is one of the most common oral health problems among preschool children, often causing pain, difficulty in chewing, and reduced food intake, which in turn may affect their nutritional status. This study aimed to determine the relationship between dental caries and nutritional status among children at Darul Imarah Kindergarten, Aceh Besar District. An analytical study with a cross-sectional design was conducted, involving 35 children aged 4–5 years selected using purposive sampling. Nutritional status was assessed through weight and height measurements using the Dietducate application, while dental caries was evaluated using the def-t index. Data analysis was performed using the Chi-Square test with SPSS software. The study was conducted between April and November 2025, including several stages such as obtaining research permits, preparing informed consent, measuring children’s weight and height, calculating body mass index, and assessing dental caries using the def-t index. The results showed a significant relationship between dental caries and nutritional status (p = 0.003; p < 0.05). In conclusion, dental caries is significantly associated with children’s nutritional status. Therefore, parents are encouraged to pay greater attention to their children’s oral health by ensuring regular dental check-ups and promoting the habit of brushing teeth twice daily.